2010
DOI: 10.1007/s11064-010-0144-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Astrocytes Crosstalking: Implications for Brain Development and Pathology

Abstract: Flavonoids are naturally occurring polyphenolic compounds that are present in a variety of fruits, vegetables, cereals, tea, and wine, and are the most abundant antioxidants in the human diet. Evidence suggests that these phytochemicals might have an impact on brain pathology and aging; however, neither their mechanisms of action nor their cell targets are completely known. In the mature mammalian brain, astroglia constitute nearly half of the total cells, providing structural, metabolic, and trophic support f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 143 publications
(126 reference statements)
0
21
0
2
Order By: Relevance
“…The effects of flavonoids being natural polyphenolic antioxidant compounds in brain development, neuroprotection and glial tumor formation are mentioned and developing new therapeutic approaches was discussed (Nones et al;. Epigallocatechin-3-gallate (EGCG) from green tea, curcumin from turmeric, and resveratrol from grapes are some examples of polyphenols.…”
Section: Therapy Via Natural Antioxidantsmentioning
confidence: 99%
“…The effects of flavonoids being natural polyphenolic antioxidant compounds in brain development, neuroprotection and glial tumor formation are mentioned and developing new therapeutic approaches was discussed (Nones et al;. Epigallocatechin-3-gallate (EGCG) from green tea, curcumin from turmeric, and resveratrol from grapes are some examples of polyphenols.…”
Section: Therapy Via Natural Antioxidantsmentioning
confidence: 99%
“…Recent interest has been focused on dietary phenolic antioxidants, such as carotenoids, cinnamic acids and flavonoids, as potentially useful agents (Fresco et al, 2006;Uttara et al, 2009). In a study, the effects of flavonoids which are natural polyphenolic antioxidant compounds in brain development, neuroprotection and glial tumor formation are discussed and suggested to develop new therapeutic approaches (Nones et al;. Curcumin as a polyphenol gets attention in blocking brain tumor formation in a study.…”
Section: Prospects Of Antioxidant Therapymentioning
confidence: 99%
“…Flavonoids are a class of phenolic compounds widely distributed in human diet with multiple health benefits [9][10][11][12]. The biological activities of flavonoids cover a very broad spectrum, due to their neuroprotective, cardioprotective, and chemopreventive effects [10,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and animal studies have shown that flavonoids, including quercetin and rutin, are antioxidants and anti-inflammatory agents [10,11,14,17,18] and can relieve nuclear condensation, decrease oxidative stress, and strengthen the barrier integrity and functions, as well are involved in important pathways that regulate cell division and proliferation [10,[19][20][21]. On the other hand flavonoids can be harmful, exhibiting in vitro cytotoxicity to many human cell lines [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation